2013
DOI: 10.1111/cdev.12124
|View full text |Cite
|
Sign up to set email alerts
|

Swiss Children's Moral and Psychological Judgments About Inclusion and Exclusion of Children With Disabilities

Abstract: Children's judgments about inclusion and exclusion of children with disabilities were investigated in a Swiss sample of 6-, 9-, and 12-year-old children from inclusive and noninclusive classrooms (N = 422). Overall, the majority of children judged it as morally wrong to exclude children with disabilities. Yet, participants were less likely to expect the inclusion of children with mental or physical disabilities in academic and athletic contexts compared to social contexts. Moreover, older children more consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
69
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(73 citation statements)
references
References 57 publications
3
69
0
1
Order By: Relevance
“…Although not many studies have investigated the development of emotions in these contexts, the existing findings indicate a more complex picture of the development of moral emotions. For example, a study on children's emotions in contexts of exclusion of children with different disabilities found an expected developmental increase in the anticipation of moral emotions, such as guilt, to excluders, from 6 to 12 years of age (Gasser, Malti, & Buholzer, 2013).…”
Section: Developmental Research On Emotions In Contexts Of Social Excmentioning
confidence: 99%
“…Although not many studies have investigated the development of emotions in these contexts, the existing findings indicate a more complex picture of the development of moral emotions. For example, a study on children's emotions in contexts of exclusion of children with different disabilities found an expected developmental increase in the anticipation of moral emotions, such as guilt, to excluders, from 6 to 12 years of age (Gasser, Malti, & Buholzer, 2013).…”
Section: Developmental Research On Emotions In Contexts Of Social Excmentioning
confidence: 99%
“…Based on a sample of 442 children from Switzerland, the researchers studied how 6-, 9-, and 12-year-old children judge and feel about exclusion based on disabilities (Gasser et al, 2014). Overall, the majority of children judged as morally wrong to exclude children with mental or physical disabilities.…”
Section: Integrating Group-level and Individual-level Modelsmentioning
confidence: 99%
“…(B) Expected moral emotions to excluders of children with physical disabilities by age group and situational context (i.e., social vs. athletic). (A) Reprinted data fromGasser et al (2014). (B) Reprinted data fromGasser et al (2014).…”
mentioning
confidence: 99%
“…Only recent research has investigated how kindergarten and elementary school children (6-to 12-years-old) balance these considerations in situations describing inclusion and exclusion on the basis of disability (Diamond & Tu, 2009;Gasser, Chilver-Stainer, Buholzer, & Perrig-Chiello, 2012;Gasser, Malti, & Buholzer, 2013a, 2013b. This research has revealed that the majority of children condemned social exclusion based on disability for moral reasons.…”
Section: Social Exclusion and Inclusion In Childhood And Adolescencementioning
confidence: 99%